2012
DOI: 10.1186/1743-7075-9-59
|View full text |Cite
|
Sign up to set email alerts
|

Zinc, vitamin A, and vitamin C status are associated with leptin concentrations and obesity in Mexican women: results from a cross-sectional study

Abstract: BackgroundThe prevalence of obesity among Mexican women is high and it could be related to micronutrient status. We evaluated in a cross-sectional study the associations of zinc and vitamins A, C and E concentrations with BMI, central adiposity, body fat and leptin concentration.MethodsWomen aged 37 ± 7.5 years (n = 580) from 6 rural communities in Mexico were evaluated. Anthropometric measurements included weight, height, waist and hip circumference. A fasting blood sample was taken for the analysis of glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 37 publications
6
80
0
10
Order By: Relevance
“…Previous studies on nutrient patterns have reported similar associations with different types of cancer [4-6, 9, 10, 26, 32] and osteoporosis [11]. Nutrients included in nutrient pattern analyses in previous studies varied between 19 and 30 nutrients and differed amongst studies based on the outcome variable(s) of interest. We attempted to include a maximum number of obesity-related nutrients and bioactive compounds (38 in total) in our analysis.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous studies on nutrient patterns have reported similar associations with different types of cancer [4-6, 9, 10, 26, 32] and osteoporosis [11]. Nutrients included in nutrient pattern analyses in previous studies varied between 19 and 30 nutrients and differed amongst studies based on the outcome variable(s) of interest. We attempted to include a maximum number of obesity-related nutrients and bioactive compounds (38 in total) in our analysis.…”
Section: Discussionmentioning
confidence: 81%
“…Obesity is one of the leading preventable risks for global deaths, and considered as an important risk factor for a number of chronic diseases, including diabetes, cardiovascular diseases and certain cancers [12]. A direct association between certain nutrients, particularly dietary fat [15] and carbohydrates [16], and the risk of obesity has been reported, while consumption of dietary proteins [17] and fiber [18], or individual micronutrients, including vitamins A, B, C [19,20] and D [21], and minerals, such as calcium [22], has been inversely related to obesity. In contrast, we are unaware of any studies examining associations between patterns of nutrient intake with obesity.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies were conducted in the USA [17,23,[27][28][29] but also in Australia [4], Brazil [15,16,30], Chili [19], Finland [31], France [32,33], India [6], Israel [24], Italy [1], Japan [2], Mexico [34], New Zealand [14], Norway [8,26], Spain [10], Sweden [7,35], Swiss [13], Thailand [25], Taiwan [21,22], Turkey [18,20], and UK [5]. Twenty-three studies measured BMI as primary outcome but additional outcomes included weight z score, weight-for-length/height z score (WHZ) (children) [13,14,16,19], abdominal sagittal diameter [35], and percentage body fat [6,7,34]. Eleven studies were deemed of good quality and 20 studies were considered as having fair quality.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…No México, Garcia et al 39 identificaram, após análise de dados transversais, que mulheres com obesidade abdominal apresentavam consumo de vitamina A mais inadequado quando comparadas com mulheres sem obesidade. Nos Estados Unidos, Maki et al 9 , analisando dados longitudinais, encontraram associação inversa entre o consumo insuficiente de vitamina D e valores elevados da CC em adultos.…”
Section: Variáveisunclassified